Optimalisasi Media Sosial Sebagai Sarana Promosi Produk Pertanian Desa - Nisa Dienwati; Nana Suarna; Achmad Fikri Ulumudin; Achmad Luthfi (CV. Multi Kreasi Media, 2023)
The agricultural sector in villages has great potential to produce high-quality products but still faces challenges in marketing. One major issue is the limited knowledge and skills of farmers in utilizing social media as a promotional tool. Through this community service program, training and mentoring were provided to farmers and agricultural entrepreneurs to enhance their understanding of digital marketing. Activities included the creation and management of business social media accounts, training in creating engaging promotional content (photos, videos, and copywriting), and branding and packaging strategies. The program showed significant improvements in farmers' abilities to market their products independently through platforms such as Instagram, Facebook, and WhatsApp Business. Farmers who previously relied solely on middlemen have now started to sell directly to consumers online. Some partners also reported increased sales and social media engagement. Additionally, the formation of a digital farmer community strengthened promotional networks and experience sharing among agricultural players. This program not only encouraged independent marketing but also enhanced the competitiveness of local agricultural products in broader markets. The program's sustainability is strongly recommended through follow-up mentoring, paid advertising training, and improved digital infrastructure in rural areas. Thus, using social media as a promotional tool becomes not just a short-term solution but a sustainable strategy to drive rural digital economic growth.